Aplikasi Metode Accelerated Failure Time (AFT): Analisis Risiko Prepayment pada Kredit Kendaraan Bermotor - Yessy Noviyanti Kawi; Yogo Purwono (IPM2KPE, 2022)
This study aims to measure the probability distribution of the time of payment in advance and explain the factors that can affect the risk of credit loans using the life analysis method. This research method is descriptive quantitative method. The sample of this research is motor vehicle loan financing debtors from private banks in Indonesia with an observation period between 2017-2019. The results of the study indicate that there is a 50% chance that the debtor of motorcycle and car loan financing will have an upfront payment after 21 months and 24 months from the initial loan application period. After the 44th and 68th months, the estimated probability of the debtor having a prepayment is > 99%. In conclusion, the tenor factor, credit limit, occupation, income, gender, marital status, age, and education level affect the variation in time until the payment in advance for motorcycle credit financing. Meanwhile, in addition to these factors, the additional factor of the area of ​​residence also affects the variation in the time of advance payments for car loans. Keywords: Survival Analysis, Banking, Credit Loans, Accelerated Failure Time, Prepayment Time